The science of sustainable development: local livelihoods and the global environment - Sayer, Jeffrey A.; Campbell, Bruce M. (Cambridge University Press, 2004)
This book attempts to redefine roles of government agencies, development assistance programmes and science in achieving a more sustainable future of rural landscapes in tropical developing countries. Science faces major challenges in tackling the inter-linked problems of poverty and environmental sustainability. This book reviews how practical science can be applied to real-life conservation and development problems, and aims to demystify the sometimes obscure science of natural resources management, interpreting it for the benefit of those who need to deal with the day-to-day problems of managing complex natural resource systems. The book responds to needs expressed by the Convention on Biological Diversity, the Global Environment Facility and many other international fora where the problems of conserving the environment in poor countries are debated. It gives practical guidance to those who design and manage conservation programmes and demonstrates that new technologies are now available that enable integrated natural resource management to move from a theory to a reality. The threats to the natural environment posed by globalisation require an integrated response that can yield real benefits to those living in tropical developing countries, whilst also achieving global environment objectives.